Growing a 'cosmic beast': observations and simulations of MACS J0717.5+3745. Issue 3 (31st August 2018) - Jauzac, M; Eckert, D; Schaller, M; Schwinn, J; Massey, R; Bahé, Y; Baugh, C; Barnes, D; Dalla Vecchia, C; Ebeling, H; Harvey, D; Jullo, E; et al.
ABSTRACT: We present a gravitational lensing and X-ray analysis of a massive galaxy cluster and its surroundings. The core of MACS J0717.5+3745 ($M(R\lt 1\, {\rm Mpc})\sim$ $2 × 10^{15}\, \, {\rm M}_{\odot }$, $z$ = 0.54) is already known to contain four merging components. We show that this is surrounded by at least seven additional substructures with masses ranging $3.8{-}6.5× 10^{13}\, \, {\rm M}_{\odot }$, at projected radii 1.6–4.9 Mpc. We compare MACS J0717 to mock lensing and X-ray observations of similarly rich clusters in cosmological simulations. The low gas fraction of substructures predicted by simulations turns out to match our observed values of 1–$4{{\ \rm per\ cent}}$ . Comparing our data to three similar simulated haloes, we infer a typical growth rate and substructure infall velocity. That suggests MACS J0717 could evolve into a system similar to, but more massive than, Abell 2744 by $z$ = 0.31, and into a ∼ $10^{16}\, \, {\rm M}_{\odot }$ supercluster by $z$ = 0. The radial distribution of infalling substructure suggests that merger events are strongly episodic; however, we find that the smooth accretion of surrounding material remains the main source of mass growth even for such massive clusters.